Mastering XPages : a step-by-step guide to XPages application development and the XSP language - Donnelly, Martin, 1963- (IBM Press, 2014)
XPages instantly revolutionized Notes/Domino application development, and the newest versions deliver unprecedented performance and flexibility. This guide to XPages development has been updated and expanded to reflect all these improvements, through IBM Notes/Domino 9.0.1 and beyond. The authors have added several hundred pages of new content, including four new chapters, presenting new tips, samples, and best practices reflecting the platform's growing maturity. Writing for both XPages newcomers and experts, they cover the entire project lifecycle, including problem debugging, performance optimization, and application scalability. This second edition fully addresses enhancements to the XPages data sources for Domino views and documents; the latest XPages mobile library; the new Domino Designer Server-Side JavaScript debugger; and improvements to integrated technologies such as Dojo and CKEditor. Nearly every chapter contains at least one downloadable sample application, offering extensive hands-on practice. This guide concludes with complete references to XSP tags, relevant Java/JavaScript classes, and XSP style classes.